Adverse Cardiovascular Effects of Phenylephrine Eye Drops Combined With Intravenous Atropine - Li, Qingyu; Pang, Jianxin; Deng, Yang; Zhang, Shaochong; Wang, Yong; Gao, Yang; Yuan, Xiaoyong; Wei, Yantao; Zhang, Hongbin; Tan, Junlian; Chi, Wei; Guo, Wenjun (Frontiers in Pharmacology, 2021)
Background: Phenylephrine and atropine can cause serious adverse effects when applied in combination. We investigated the effect of phenylephrine eye drops combined with intravenous atropine on the cardiovascular system in patients under general anesthesia undergoing intraocular surgery. Methods: The effects of the drugs were observed through clinical study. Thirteen patients undergoing intraocular surgery under general anesthesia were observed in this study; all were injected intravenously with atropine due to the oculocardiac reflex during surgery. To study the combination of drugs, an in vivo study was performed on rats. Seventy-two standard deviation rats that received phenylephrine eye drops and intravenous atropine treatment under general anesthesia were assessed, of which 18 treated with these drugs simultaneously were administered normal saline, neostigmine or esmolol. Blood pressure and heart rate were recorded and analyzed. Findings: The age of the patients ranged from seven to 14 years old with an average age of 10.7 years old, and 11 patients were male. In patients, 5% phenylephrine eye drops combined with intravenous atropine led to a significant heart rate increase and the increase lasted 20 min. The significant increase in diastolic blood pressure and systolic blood pressure lasted for 15 and 25 min, respectively. From five to 25 min after intravenous atropine treatment, the systolic blood pressure and diastolic blood pressure were both more than 20% higher than that at baseline. In rats, the changes in blood pressure and heart rate were independent of the phenylephrine and atropine administration sequence but were related to the administration time interval. The neostigmine group showed a significant decrease in blood pressure after the increase from the administration of phenylephrine and atropine. Interpretation: Phenylephrine eye drops combined with intravenous atropine have obvious cardiovascular effects that can be reversed by neostigmine. This drug combination should be used carefully for ophthalmic surgery, especially in patients with cardio-cerebrovascular diseases.